The Constructive Contexts of the Artistic Profile of Nations and populations - Bouchareb, Fouzia (Journal of Humanities & Social Sciences, 2023)
Art is considered as a complex human phenomenon which existed with Man and developed with his development. Art is characterized by its audacity and strength when dealing with human issues that goes deep in the human self, the proposal that was impossible to deal with in other sciences; only Art could cover those issues and present them to public. However, it kept being the product of its social, cultural and religious environment, this environment gave art its own profile. From this point, we have explained the contribution of some models in constructing some artistic profiles of populations and nations, the profile that constitutes their specificity and their socio-cultural touch that makes them different from others, this fact doesn’t deny the existence of some common points between the different nations and populations since art is a human phenomenon shared between all people. We have seen the existence of six Contexts based on constructing the artistic profile of every nation and population; we summarized them in the civilization development within the means of protecting the artistic heritage, in this frame we adopted the Marshall Mc Luhan theory, the innovative traditions and the critic traditions Context, the social necessity and the insistence of the socio-cultural reality Context, the cumulative artistic appreciation experiences Context, the use and the satisfaction modal and last the political and the authoritarian influence Context.
Keywords: profile; art; Contexts; the artistic appreciation; the creative traditions; the critic traditions